Health education projects in Portuguese schools: A multicases study - Oliveira, Hugo (2020)
Health education projects (HEP) incorporate all the educational projects of the Portuguese elementary and secondary schools in order to respond to four key areas: mental health and violence prevention; food education and physical activity; addictive behaviors and dependencies; and affection and sexuality education. This study aimed at identifying the effects of HEP as they are perceived by teachers and students. A multicase study was developed in five schools in the municipality of Castelo Branco, Portugal. The sample consisted of a HEP coordinating teacher and one student from each case. The content analysis of each HEP was performed and semi-structured interviews were conducted with the participants. The analysis of the information showed that HEPs induce positive changes in the educational community lifestyle, and especially in students. Despite this positive view, targeted areas were diagnosed for optimization processes in each of the four dimensions of the HEPs being studied. This allowed the different projects to qualitatively improve their performance among the target audience. The investigations acknowledged the lack of instruments and methodologies able to record the behavioral changes developed within the scope of health education (HE) while simultaneously stimulating reflection on these behavioral changes and their causes.